2021
DOI: 10.1001/jamainternmed.2020.5950
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Nurse-Led Multidisciplinary Intervention vs Usual Care on Advance Care Planning for Vulnerable Older Adults in an Accountable Care Organization

Abstract: Advance care planning (ACP), especially among vulnerable older adults, remains underused in primary care. Additionally, many ACP initiatives fail to integrate directly into the electronic health record (EHR), resulting in infrequent and disorganized documentation.OBJECTIVE To determine whether a nurse navigator-led ACP pathway combined with a health care professional-facing EHR interface improves the occurrence of ACP discussions and their documentation within the EHR. DESIGN, SETTING, AND PARTICIPANTSThis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 62 publications
(113 reference statements)
0
52
0
4
Order By: Relevance
“…McMahan et al 22 conducted a scoping review of ACP outcomes such as quality of care, patient/surrogate/clinician satisfaction with communication, and surrogate satisfaction with patients' care, but did not focus on HH nor include hospitalization specifically. Gabbard et al 23 found incidences of hospitalization were similar between randomized groups in their study of ACP outcomes among patients 65 years or older in a primary care accountable care organization, but this was not specific to HH nor agency ACP protocols. The Arbor Research Collaborative was contracted by CMS to study the impacts of the HHVBP program, which included hospitalization, but their studies in the Third Annual Report of the Evaluation of the Home Health Value-Based Purchasing Model 14 did not examine the role of ACP.…”
Section: Discussionmentioning
confidence: 95%
“…McMahan et al 22 conducted a scoping review of ACP outcomes such as quality of care, patient/surrogate/clinician satisfaction with communication, and surrogate satisfaction with patients' care, but did not focus on HH nor include hospitalization specifically. Gabbard et al 23 found incidences of hospitalization were similar between randomized groups in their study of ACP outcomes among patients 65 years or older in a primary care accountable care organization, but this was not specific to HH nor agency ACP protocols. The Arbor Research Collaborative was contracted by CMS to study the impacts of the HHVBP program, which included hospitalization, but their studies in the Third Annual Report of the Evaluation of the Home Health Value-Based Purchasing Model 14 did not examine the role of ACP.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, these reviews found no association of ACP with subsequent health care use, including emergency department visits, hospitalizations, and critical care. Subsequently, 5 large multisite randomized clinical trials that enrolled patients with cancer (1117 patients at 23 hospital cancer centers), 3 nursing home residents (12 479 residents from 360 nursing homes), 4 older adults in primary care (759 patients from 8 primary care practices), 5 adults with serious illness (515 patients from 20 outpatient clinics), 6 and patients with heart failure (282 patients from 2 heart failure centers) 7 could not identify meaningful differences in health care use, patient quality of life, or goal-concordant care between those randomly assigned to receive either ACP or usual care.…”
mentioning
confidence: 99%
“…The ACP discussion requires the cooperation of a multidisciplinary team, in which health care professionals, lawyers, psychologists, social workers, and others all play an important role. This multidisciplinary team should help elderly AIDS patients initiate ACP discussions at the right time, maintain patient autonomy, and improve quality of life and sense of dignity at the end of life 38 . To promote ACP discussions among elderly AIDS patients, the circular support system from educational institutions to social institutions and medical institutions should be established.…”
Section: Discussionmentioning
confidence: 99%